Adult-onset hypothyroidism induces granulosa cell apoptosis and affects ovarian follicle development in rats - Li, Shuyue; Zhang, Lina; Li, Wanqiong; Qin, Jiaying; Qi, Lingbin; Xiao, Xi; Xue, Zhigang; Xue, Jinfeng; Ji, Yazhong (Frontiers in Cell and Developmental Biology, 2025)
IntroductionHypothyroidism is a common endocrine disorder in women, which could lead to ovulation disorders and infertility, however, the effects of adult-onset hypothyroidism on ovarian development and gene expression characteristics need further study.MethodsHere we conducted an adult-onset hypothyroidism rat model by using the methimazole (MMI) induction, then the hormone level changes and ovarian development were evaluated, furthermore, the effects of gene expression of granulosa cells and oocytes were detected by using single-cell RNA sequencing.ResultsOur results showed that, in addition to a decrease in thyroid hormones, the body weight was significantly reduced, while the estrus cycle was prolonged in the hypothyroidism group. Although the ovary/body weight ratio was not changed, the adult-onset hypothyroidism disrupted follicle development, primarily manifested by an increased number of atretic follicles and a decreased number of corpora lutea. Serum sex hormone levels were also imbalanced, with elevated LH, FSH, and PRL, while E2 and P were decreased. By combining single-cell RNA sequencing and the validation experiments, we found that adult-onset hypothyroidism promoted apoptosis in granulosa cells of antral follicles and induced oxidative stress in oocytes. Notably, we found significant heterogeneity in mitochondrial ROS in the control group, indicating differences in the redox status of different normal oocytes, which disappeared after hypothyroidism promoted oxidative stress.DiscussionIn conclusion, adult-onset hypothyroidism interferes with normal follicle development and impairs fertility by promoting apoptosis in granulosa cells of antral follicles and inducing oxidative stress in oocytes.